2001
DOI: 10.4038/jnsfsr.v29i3-4.2613
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of essential oil constituents of bark, leaf, root and fruit of cinnamon (Cinnamomum zeylanicum Blum) grown in Sri Lanka

Abstract: Abstract:The essential oils of the bark, leaf, root and fruit of Cinnamon were analyzed by capillary GC and GCIMS. The major constituents of Cinnamon fruit oil, were 6-and y-cadinene (36.0%) and T-cadinol (7.7%) and 8-caryophyllene (5.6%). About 84% of Cinnamon fruit oil comprised sesquiterpenes while other parts of Cinnamon contained less than 9% of this group of compounds. Phenyl propanoids were the major constituents of Cinnamon bark and leaf oils while root oil had monoterpenes as the major constituents (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 3 publications
7
45
0
1
Order By: Relevance
“…GC‐MS analysis showed that the major component of cinnamon leaf oil used in this study was eugenol, which was 84·5% of the total oil composition. This is similar to findings in the current literature (Mallavarapu et al ; Paranagama et al ; Raina et al ; Jayawardena and Smith ). In contrast, the major component of the cinnamon bark EO used in this study was Σ‐cinnamaldehyde at 85·3% of the total composition.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…GC‐MS analysis showed that the major component of cinnamon leaf oil used in this study was eugenol, which was 84·5% of the total oil composition. This is similar to findings in the current literature (Mallavarapu et al ; Paranagama et al ; Raina et al ; Jayawardena and Smith ). In contrast, the major component of the cinnamon bark EO used in this study was Σ‐cinnamaldehyde at 85·3% of the total composition.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, the major component of the cinnamon bark EO used in this study was Σ‐cinnamaldehyde at 85·3% of the total composition. The high levels of this component in the bark EO has been demonstrated in other studies (Paranagama et al ; Jayawardena and Smith ; Shahina et al ). This contrasting composition of the two oils provides an explanation of their different antimicrobial effects, and it has been shown that cinnamaldehyde has a superior antimicrobial effect when compared to eugenol (López et al ; Sanla‐Ead et al ; Brnawi et al ).…”
Section: Discussionsupporting
confidence: 72%
“…The major compounds eugenol, cinnamaldehyde, β‐caryophyllene, linalool, cinnamyl acetate, benzyl benzoate, eugenyl acetate, ( E )‐ethyl cinnamate, alcohol cinnamyl acetate, camphor, linalool, and piperitone have been reported from essential oils derived from the leaves of C zeylanicum . More than two decades ago, however, seasonal variation in the essential oil from leaves of C zeylanicum was reported for three different months of harvest .…”
Section: Introductionmentioning
confidence: 99%
“…The main chemical component present is Eugenol. Cinnamomum verum bark contains major components [19] cinnamaldehyde and eugenol. It lowers blood sugar levels, reduces heart disease risk factors and has other health benefits.…”
Section: Introductionmentioning
confidence: 99%